OSTRACODS FROM THE GLOBAL STRATOTYPE SECTION FOR THE BASE OF THE AALENIAN STAGE, JURASSIC AT FUENTELSAZ SECTION(CORDILLERA IBÉRICA, SPAIN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The Toarcian/Aalenian Global Stratotype Section and Point (GSSP) have been recently placed in the Fuentelsaz section, northeastern Spain. This paper is part of a long-term project that attempts to describe for the first time the fossil ostracod assemblages present in the Toarcian-Aalenian boundary GSSP, and to assess their palaeobiogeographical significance. The study of the Late Toarcian-Early Aalenian Turmiel and Casinos formations at the Fuentelsaz section has produced a detailed stratigraphy and a large collection of stratigraphically constrained ostracod faunas. Twenty benthic ostracod species have been identified and for the first time described in Spain. Higher part of the Mactra Subzone, Late Toarcian, have yielded abundant ostracod faunas, including mostly species of the genera Praeschuleridea, Cytherelloidea and Kinkelinella; fossiliferous marls of the Late Toarcian and part of the Early Aalenian and poorly fossiliferous marls at the beginning of the Opalinum Zone are dominated by Praeschuleridea and Cytherelloidea. The boundary between the Toarcian and Aalenian is not characterized by any radical change in the ostracod faunal composition. The Fuentelsaz sequence exhibits ostracod assemblages comparable to those recorded in western Europe, with many of their species having similar stratigraphical distributions.
Keywords: Toarcian–Aalenian boundary; Fuentelsaz section; Stage boundary stratotype; Ostracoda; Taxonomy; Palaeogeography; Spain